We are the Poors: Community Struggles in Post-Apartheid South Africa - Wood, Geoffrey (Labour / Le Travail, 2003)
The article reviews the book, "We Are the Poors: Community Struggles in Post-Apartheid South Africa," by Ashwin Desai.
Keywords: BOOKS – Reviews; DESAI; Ashwin; Nonfiction; SOUTH Africa; WE Are the Poors: Community Struggles in Post-Apartheid South Africa (Book)